1980
DOI: 10.1038/288280a0
|View full text |Cite
|
Sign up to set email alerts
|

A new class of angiotensin-converting enzyme inhibitors

Abstract: Much current attention focuses on the renin-angiotensin system in relation to mechanisms controlling blood pressure and renal function. Recent demonstrations (ref. 1, ref. 2 and refs therein) that angiotensin-converting enzyme inhibitors show promising clinical antihypertensive properties have been of particular interest. We now report on the design of a novel series of substituted N-carboxymethyl-dipeptides which are active in inhibiting angiotensin-converting enzyme at nanomolar levels. We suggest that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
268
0
5

Year Published

1982
1982
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 710 publications
(280 citation statements)
references
References 13 publications
7
268
0
5
Order By: Relevance
“…Studies of ACE inhibition with rabbit lung homogenates (Table 1) and guinea pig ileum (Table 2) indicated that CV-5975 is a potent ACE inhibitor. The IC50 value of enalaprilat on the lung ACE was compatible with the published values (17,18). CV-5975 aug mented the BK-induced contraction of the guinea pig ileum more potently than did enalaprilat, but inhibited the A-I-induced con traction of the ileum to much the same extent as enalaprilat did (Table 2).…”
Section: Discussionsupporting
confidence: 78%
“…Studies of ACE inhibition with rabbit lung homogenates (Table 1) and guinea pig ileum (Table 2) indicated that CV-5975 is a potent ACE inhibitor. The IC50 value of enalaprilat on the lung ACE was compatible with the published values (17,18). CV-5975 aug mented the BK-induced contraction of the guinea pig ileum more potently than did enalaprilat, but inhibited the A-I-induced con traction of the ileum to much the same extent as enalaprilat did (Table 2).…”
Section: Discussionsupporting
confidence: 78%
“…Certain inhibitors of angiotensin-converting enzyme (ACE, EC 3.4.15.1) which transforms the decapeptide angiotensin I to the powerful vasoconstrictor octapeptide angiotensin II offer promise as therapeutic agents. Useful antihypertensive properties have been demonstrated, clinically, for the nonapeptide SQ 20 881 and the orally-active inhibitors captopril (SQ 14 225,I) [I] and MK 421 (enalapril II) [2]. The two latter compounds are very active inhibitors of ACE in vitro (table 2).…”
Section: Introductionmentioning
confidence: 99%
“…tulated zinc atom in the enzyme while retaining a close similarity to the dipeptide Ala-Pro. The compound MK 421, which includes an Ala-Pro fragment in the molecule was the outcome of extensive structure-activity studies; it is visualised as a transition stage analogue inhibitor [2].…”
Section: Introductionmentioning
confidence: 99%
“…Enalapril maleate is a new orally active converting enzyme inhibitorwith no sulfhydryl group in its molecular structure (1,2). Acute and chronic effect of enalapril on blood pressure (BP) has been examined in hyper tensive animals, including spontaneously hypertensive rats (SHR) and renal hyper tensive rats or dogs (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%